PENATALAKSANAAN FISIOTERAPI DALAM PENINGKATAN FUNGSI SEKSUAL DENGAN METODE LATIHAN SENAM SEKSIOLOGI DAN KEGEL EXERCISE PADA IBU MULTIPARA PASCA PERSALINAN PERVAGINA - Sabila Maharani, Anggi; Junaidi, Adi Saputra; Suherman, Ucu (Prodi Fisioterapi UFDK, 2023)
The base of the pelvis is a complex of tissue that lies between peritoneum viseralis and the vulva skin, which plays a role in supporting viseralis’ organ s in the pelvis to remain in position and function normally resulting in reduced muscular underside of the pelvic base or pudendal nerve asa result of labor from the labor of the baby’s head on the vagina.Objektive: To determine the management of physiotherapy in increasing sexual function with the method of sexiology gymnastics and kegel exercise of mom multiport-natal pervaginas.Result: After 14 treatments, the results were obtained, there was an increase in pelvic floor muscle strength and an increase in female sexual function. Based on the graph of pelvic floor muscle strength as measured by a perineometer, it can be seen that the effect of giving exercise is from T0 6 mmHg, T6 16 mmGg, dan T14 30 mmHg. Then the graph of pelvic floor muscle strength as measured by vaginal palpation can be seen the effect of giving exercise, namely from T0 2, T6 3, dan T14 4. From the results of the graph of sexual function as easured by the FSFI questionnaire, it can be seen that there is an increase in the patient’s sexual function, namely T0 26,6 to T14 29,7.Conclusion: Sexiological Gymnastics and Kegel Exercise can increase the sexual function and elementary tenets of the pelvic floor muscle strength.Keywords: Sexual Function, Sexiology Exercise, and Kegel Exercise